2004
DOI: 10.1111/j.1467-6443.2004.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex in Health Education: Official Guidance for Schools in England, 1928–1977

Abstract: This article examines official policy discourses on sex within the health education curriculum of schools during the period 1928-77. The article begins with an account of the origins of sex education in schools, and of why, in the early twentieth century, its inclusion in the health education curriculum was problematical. In the main section, the article examines the content of consecutive editions of the government published "handbooks of health education", and of an important supplementary guidance pamphlet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…As Pilcher (2004) has noted, government policy on school-based sex education became much more explicit at the beginning of the 1940s, and the arguments in favour of sex education in HEJ are consistent with the wider concerns surrounding the 'lowering of moral standards inevitable in war-time' (Ewing, 1944) which inspired this new focus on sex education.…”
Section: S: War-time Immorality and Venereal Diseasementioning
confidence: 97%
See 3 more Smart Citations
“…As Pilcher (2004) has noted, government policy on school-based sex education became much more explicit at the beginning of the 1940s, and the arguments in favour of sex education in HEJ are consistent with the wider concerns surrounding the 'lowering of moral standards inevitable in war-time' (Ewing, 1944) which inspired this new focus on sex education.…”
Section: S: War-time Immorality and Venereal Diseasementioning
confidence: 97%
“…These papers suggest that a 'no-nonsense' approach to sex education was seen as the best approach to adopt during the period (which is also noted by Reiss (2005) and Pilcher (2004) in their reviews of contemporaneous sex education policies), particularly as a means to ensure that girls and boys were prepared for their respective roles in the family. Notions of 'normal' and 'abnormal' sexual activity are also firmly established in these articles.…”
Section: S: Sex Education and The Familymentioning
confidence: 99%
See 2 more Smart Citations
“…This depiction of sexuality as a potentially destructive force is an articulation of official concerns about the impact of conditions of war on the morality of the nation, which had led to the publication of the pamphlet in the first place. 61 Nonetheless the report did aim to advise teachers on how to provide sex education although it did not dictate specific aims or methods. It was suggested that the approach to sex education be guided by the age and understanding of the child.…”
Section: A Davismentioning
confidence: 98%